DDEL-06. Drug Delivery to the Pons Using Short-Pulse Focused Ultrasound and Microbubble Exposure for the Treatment of Diffuse Midline Glioma. (3rd June 2022) - Chattenton, Dani; Rivens, Ian; Jiang, Zheng; Carvalho, Diana M; Sujarittam, Krit; Boult, Jessica K R; Robinson, Simon P; Jones, Chris; ter Haar, Gail; Choi, James
Abstract: Despite advances in understanding diffuse midline glioma (DMG-H3K27), including DIPG, there are still no effective treatments available, and the dismal clinical prognosis remains. This is partly because of tumour spread behind an intact blood brain barrier (BBB), preventing drug delivery and the reason for many drugs failing in the clinic. The use of focused ultrasound and intravenous microbubbles enables temporary increases in BBB permeability, allowing drugs to enter the targeted brain region. Building on recent research demonstrating that short pulses (<5 µs) of ultrasound can deliver drugs safely and uniformly to the hippocampus, we evaluated whether a similar result was achievable in the pons of mice. Mice were exposed to ultrasound (peak-negative pressure: 0.4 MPa, pulse length: 5 cycles, centre frequency 1 MHz) emitted in bursts of 38 pulses. During exposure mice received an intravenous injection of SonoVue(R) microbubbles and a fluorescently-tagged tracer (dextran, 3 kDa), acting as a drug mimic. Dextran was successfully delivered to the pons of non-tumour-bearing mice assessed by fluorescence microscopy immediately post-treatment. Dextran delivery was repeatable and confined to the targeted pons region with a homogenous distribution, typical of short pulse ultrasound, and important for treating DMG to ensure all tumour cells receive an equal drug dose. No damage to the brain was observed after H&E staining. Panobinostat has shown promise in vitro but tolerated doses have not shown therapeutic benefit in vivo as it does not cross the BBB. The in vitro toxicity of panobinostat was confirmed in a Nestin-Tv-a/p53fl/fl, RCAS-ACVR1R206H + RCAS-H3.1K27M murine cell line, with a GI50 of 15.56 nM. The ability of focused ultrasound to deliver panobinostat across the BBB to these tumours grown orthotopically will be assessed. Overall, we hope to develop a drug delivery system, that enables therapeutics to cross the BBB, expanding treatment options for DMG.